Musculoskeletal function and phenotyping in frail older patients having hip surgery following fracture - Ikram, Adeel (2024)
A hip fracture is a catastrophic injury to an elderly individual with a significant impact individually, on the family, and for health care services. Despite optimisation of medical comorbidities, effective skilled anaesthesia, and early surgery, the patient important outcomes of mobility, independence, and mortality have not improved. With an aging population comes increasing frailty, and those who are frail have the worst outcomes. However, frailty in existing literature has been difficult to quantify. Multiple methods have been used to ascertain and classify frailty status, utilising two different schools of thought: cumulative deficits and phenotype models. Frailty is the ability for an individual to bounce back from illness or injury. It is not known why those who are frail have the worst outcomes and what biological processes occur which underpin these poor outcomes in these individuals.